SUBSYNCHRONOUS RESONANCE OF DEEP-BAR INDUCTION-MOTORS - Limebeer, D; Harley, R (1981)
Results of an investigation into the subsynchronous resonance (SSR) instability of deep-bar induction motors when supplied through series capacitor compensated feeders are presented. As in a companion study published by the authors on single-cage induction motors, physical insight into SSR instability is obtained from a simple equivalent circuit analysis and the discrete Fourier transforms of some of the transient waveforms. The main contribution of this paper is to show that, provided the stator resistance is below some minimum value, an unstable region will exist between an upper and lower resonant speed, as in the case of a single-cage motor.